Rejoinder - Bryan, Michael F.; Cecchetti, Stephen G. (The Review of Economics and Statistics, 1999)
May 01 1999 Rejoinder Michael F. Bryan, Michael F. Bryan Search for other works by this author on: This Site Google Scholar Stephen G. Cecchetti Stephen G. Cecchetti Search for other works by this author on: This Site Google Scholar Author and Article Information Michael F. Bryan Stephen G. Cecchetti Received: December 16 1998 Accepted: December 18 1998 Online ISSN: 1530-9142 Print ISSN: 0034-6535 © 1999 President and Fellows of Harvard College and the Massachusetts Institute of Technology1999 The Review of Economics and Statistics (1999) 81 (2): 203–204. https://doi.org/10.1162/003465399558175 Article history Received: December 16 1998 Accepted: December 18 1998 Cite Icon Cite Permissions Share Icon Share Facebook Twitter LinkedIn Email Views Icon Views Article contents Figures & tables Video Audio Supplementary Data Peer Review Search Site Citation Michael F. Bryan, Stephen G. Cecchetti; Rejoinder. The Review of Economics and Statistics 1999; 81 (2): 203–204. doi: https://doi.org/10.1162/003465399558175 Download citation file: Ris (Zotero) Reference Manager EasyBib Bookends Mendeley Papers EndNote RefWorks BibTex toolbar search Search Dropdown Menu toolbar search search input Search input auto suggest filter your search All ContentAll JournalsThe Review of Economics and Statistics Search Advanced Search This content is only available as a PDF. © 1999 President and Fellows of Harvard College and the Massachusetts Institute of Technology1999 Article PDF first page preview Close Modal You do not currently have access to this content.